Paris Match colonial : variétés d’un discours de contrepoint - Laure Demougin (Contextes)
Paris Match published several famous colonial articles. Others, less known, were part of the many texts that built up, with different tones and points of view, the French colonial images, especially in the 1950s. This article aims to study a few revealing cases of this “counterpoint colonial discourse” that the magazine develops: “colonial discourse” because journalism holds a prominent place in the perception that French readers will have of their colonies through a rich background. As for “counterpoint”, it is because of the light we will shed on reportages published in parallel with the wars of decolonization, reportages that focused on a different timeline. We will aim at studying those kind of reportages that use the background of colonial literature to produce new images and new texts.